Intronic gRNAs for the Construction of Minimal Gene Drive Systems - Nash, Alexander; Capriotti, Paolo; Hoermann, Astrid; Papathanos, Phillipos Aris; Windbichler, Nikolai (Frontiers in Bioengineering and Biotechnology, 2022)
Gene drives are promising tools for the genetic control of insect vector or pest populations. CRISPR-based gene drives are generally highly complex synthetic constructs consisting of multiple transgenes and their respective regulatory elements. This complicates the generation of new gene drives as well as the testing the behavior of their constituent functional modules. Here we explore the minimal genetic components needed to constitute autonomous gene drives in Drosophila melanogaster. We first designed intronic gRNAs that can be located directly within coding transgenes sequences and tested their function in cell lines. We then integrated a Cas9 open reading frame hosting such an intronic gRNA within the Drosophila rcd-1r locus that drives expression in the male and female germline. We showed the that, upon removal of the fluorescent transformation marker, the rcd-1rd allele supports efficient gene drive. We assess the propensity of this driver, designed to be neutral with regards to fitness and host gene function, to propagate in caged fly populations. Because of their simplicity such integral gene drives could enable the modularization of drive and effector functions. We also discuss the possible biosafety implications of minimal and possibly recoded gene drives.